Comparison of Neuro-cognitive Functional Networking on Reasoning and Concept Formation between Healthy Adolescents: A Sibling Study - Baruah, Manidipa; Pal, Shraddha (International Journal of Psychosocial Rehabilitation, 2020)
Influence of sibling can have an important role during the development of a child particularly during the adolescent stage. Neuro- cognitive connection or networking between siblings are either genetic or through impact of learning and social interactions.This paper focuses on the trait of reasoning and concept formation among siblings (opposite sex) to see the significant difference between them and to explore the possibility of gender biasness on the development of reasoning and concept formation which guide the particular problem solving behavior and thought pattern towards future direction.Methodology The present study is the matched group experimental design, conducted among 20 pairs of girl and boy siblings, all resident of a particular academic campus. Random sampling method was adopted for selection. A self-developed socio demographic data sheet. It includes information like age, gender, education, socio economic details, scholastic history, Wisconsin card sorting test, and Haufmann and Kasanin concept formation experiment were used in this study. indicate that there is no significant difference between girl and boy siblings and there is no specific gender biasness on reasoning and concept formation among children.